The Effect of Su Jok Therapy on Reducing the Severity Scale of Physical Symptoms of Patients with Hypertension - Rositasari, Etik; Afifah, Nurul; Muhshanah, Muhshanah; Nurjannah, Intansari (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2024)
Introduction: Hypertension is a cardiovascular disease that causes certain signs and symptoms, causing discomfort and interfering with daily activities. One alternative therapy to reduce physical symptoms is using Su Jok Therapy. Su Jok Therapy is a complementary therapy originating from Korea. The method is by manipulating the hands or feet using different methods such as massaging, applying colour, putting seed or magnet and other methods. This research aimed to determine the effect of Su Jok Therapy on reducing the severity scale of physical symptoms of hypertensive patients. Methods: The data was collected from one of the public health centers in Bantul, Yogyakarta. There were 15 patients with hypertension, 3 males (20%) and 13 females (80%), with the most physical complaints being knee pain (38,8%). Su Jok therapy was applied using massage and seed method, lasting about 5-7 minutes. The final data was then analyzed using the Wilcoxon Signed Rank Test. Results: The result showed that the average severity scale of physical complaints before therapy was 3.20, with a standard deviation of 0.561. Meanwhile, the average complaints scale after therapy was 1.87, with a standard deviation of 0.640. The Wilcoxon Signed Rank Test analysis results show a p-value of 0.001 (p <0.05). Conclusion: It can be concluded that Su Jok Therapy can reduce the average level of severity scale of physical symptoms in a short time.